Exigibilidad del cobro de la garantía de arrendamiento en materia de inquilinato y la inseguridad jurídica causada por la inexistencia de esta figura normativa. - Colala Quito, Evelyn Dayanara (2024)
The current Curricular Integration Work acquires significant importance because a violation of pre-existing rights has been established: right to housing, right of use and habitation, right to property, and contributing to legal security, established in the Constitution of the Republic of Ecuador, it happens that despite the existence of the Tenancy Law, the figure of the collection of guarantees is non-existent, there is a lack of regulations, code and procedure, which is why its express acceptance or prohibition in the lease contract has not been affirmed. However, its practice has become normalized in Ecuadorian society, custom being a source of law that makes up for the lack of regulations. Which has generated countless controversies and abuses, especially on the part of the lessor of the real estate, since on more than one occasion they have refused to return this financial amount, even though the real estate is in optimal condition. Therefore, it is also important to consider the return mechanisms, generally taking into account the physical and structural conditions of the real estate at the time of beginning the occupation of the real estate and at the end of the lease contract. This is how the preparation of this project will make it possible to highlight the existing legal gaps in the Tenancy Law with respect to the legality and enforceability of the collection of the guarantee in lease contracts, to propose possible solutions that allow regulating the items charged for lease guarantees in order to avoid excessive charges regarding this guarantee by the tenant and even to ensure the return of the economic amount once the contract has ended and there is no need to cover any damage to the property.